Ethnozentrismus und Ökonomismus: Die »Leistungsgesellschaft« als Deutungsmuster für soziale Ausgrenzung - Hopf, Wulf (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1996)
The mticle focuses on the economic dimension of ethnocentrism and aggression towards foreigners. Interviews with right-wing and ethnocentric young adults show that they iclentify with Germany's cconomic power and accept or reject foreign citizens according to their qualifications for work, and according the purported costs they induce. These attitudes may be also found in the society at !arge, but the interviewed supporters of the extreme right, who experienced socialization distress and stait their worklife in lower positions, display them in a very restrictive and aggressive manner.